Cogeração usando gases de escapamento de motores diesel sobrealimentados, potencialidades, impactados - Pitillo, José Edmundo (2006)
Cogeneration is a broadly used tool to improve the performance of thermal systems by using combined cycles. In this sense, it is aimed to identify the amount of spare energy found in the turbine used to perform extra power in engines equipped either with waste-gate or twin flow. In this way, refrigerating power is used motor vehicle applications. For this purpose, a semiempirical model is used for the engine, as based on the Otto cycle. Consequently, considerations extracted from the thermodynamic laws are applied to the air and gas flow through the various auxiliary engine components leading to a model that permits to evaluate the behavior of the parameters that characterize the operating conditions of the engine. The models were validated according to experimental data extracted from the literature (Bermudez, 1995) for the engine operating under full charge condition. Based on simulated results, the liquid power (cogeneration power) of the turbo-compressor was calculated by considering that the discharge gases were reoriented to the waste-gate to expand in the turbine. Similarly, VGT turbines allow obtaining this eventual extra power by varying its effective flow area. Another important aspect that was evaluated in this dissertation is related to the availability of the extra energy during the operation of the engine. In this sense, it was observed that this extra power was available in the engine during 70% of its operation time, under the condition of open waste-gate.